Fire and the reproductive phenology of endangered Madagascar sclerophyllous tapia woodlands - Alvarado, Swanni T.; Buisson, Elise; Rabarison, Harison; Rajeriarison, Charlotte; Birkinshaw, Chris; Lowry, Porter P.; Morellato, Leonor P. C. [UNESP] (Elsevier B.V., 2014)
Tapia woodland vegetation is a remnant of Madagascar sclerophyllous forest that has developed under the selective pressure of fire and is dominated by the endemic tree Uapaca bojeri (Phyllanthaceae), locally named tapia. We carried out a 2-year study in tapia woodland at Ibity mountain, a new protected area in central highlands of Madagascar. We aimed to describe the reproductive phenology of this vegetation type and to determine whether it is affected by fire. We addressed two main questions; 1) does fire frequency affect the proportion of reproducing individuals and the intensity of each flowering and fruiting event?; and 2) does fire frequency influence the reproductive synchrony of species across the landscape? Thirteen woody species (373 individuals) were sampled at six sites selected across the Ibity mountain, where three that were burned three times between 2000 and 2010 and three burned just once during the decade. We found that (1) fire reduced the percentage of individuals that participate in each phenophase, and flower and fruit production was lower at the more frequently burned sites; and (2) increased fire frequency reduced the reproductive synchronization of species throughout the landscape. Fire is recognized as one of the major disturbances affecting mortality and recruitment of trees in tapia woodland. Our study indicates that fire also impacts the timing of plant reproduction at community and landscape levels. (C) 2014 SAAB. Published by Elsevier B.V. All rights reserved.
Keywords: Reproductive phenology; Fire; Tapia woodland; Uapaca bojeri; Ibity mountain